Impact of Servant Leadership on Satisfaction Levels: Role of Facilities as a Mediating Variable - Pratama, Yoni Evan; Andriadi, Taufik (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study explores the impact of Servant Leadership and workplace facilities on employee satisfaction at PT. Shark Globalindo Jaya, a company in the garment and shoe production industry. Using a quantitative approach and data from 129 employees, the study analyzes the relationships between these variables using Smart PLS 4.0. The findings reveal that Servant Leadership positively influences employee satisfaction, with its focus on employee development, empowerment, and ethical behavior. Additionally, workplace facilities, such as comfortable workspaces and adequate resources, significantly contribute to a positive work environment, enhancing employee satisfaction and performance. The study also applies the Disconfirmation of Expectations Theory, emphasizing the importance of meeting or exceeding employee expectations to reduce dissatisfaction. The results highlight the need for organizations to prioritize effective leadership and supportive facilities to foster a productive and engaged workforce.